Предмет: Алгебра, автор: RADIK5005

пожалуйста решите с графиками​

Приложения:

Ответы

Автор ответа: anna171770
0

Ответ:

Объяснение:

1. (x+12)(x-3) > 0

x + 12 = 0

x - 3 = 0

x = -12

x = 3

y(0) = (0+12)(0-3) = 12×(-3) = -36

y(-15) = (-15 + 12)(-15-3) = -3×(-18) = 54

y(4) = (4+12)(4-3) = 16×1 = 16

x∈ (-∞; -12)∪(3; +∞)

2. x(x-5)(8-x)(x+3) ≤ 0

x=0

x-5 = 0

x = 5

8-x =0

-x = -8

x = 8

x + 3 = 0

x = -3

y(-4) = -4(-4-5)(8 - (-4))(-4 + 3) = -4×(-9)×12×(-1) = -432

y(-1) = -1(-1-5)(8-(-1))(-1+3) = 108

y(1) = 1(1-5)(8-1)(1+3) = -112

y(6) = 7(7-5)(8-7)(7+3) = 140

y(9) = 9(9-5)(8-9)(9+3) = -432

x∈ (-∞; -3]∪[0; 5]∪[8; +∞)

3. (x+1)(3-x)(x-2) < 0

x+1=0

x = -1

3-x = 0

-x = -3

x = 3

x-2 = 0

x = 2

y(-2) = (-2+1)(3-(-2))(-2-2) = 20

y(0) = (0+1)(3-0)(0-2) = -6

y(2.5) = (2.5 +1)(3-2.5)(2.5 -2) = 0.875

y(4) = (4+1)(3-4)(4-2) = -10

x∈ ( -1; 2)∪( 3; +∞)

4. (x+8)(x-4) ≥ 0

x+8 = 0

x = -8

x - 4 = 0

x = 4

y( -10) = (-10 + 8)( - 10 - 4) = 28

y(0) = (0+8)(0-4) = -32

y(5) = (5+8)(5-4) = 13

x∈ (-∞; -8]∪[4; +∞)

Приложения:
Похожие вопросы